International law as behavior / edited by Harlan Grant Cohen, University of Georgia, Timothy Meyer, Vanderbilt University. - Cohen, Harlan Grant; Meyer, Timothy, 1981- (ASIL Studies in International Legal Theory., 2021)
This volume includes chapters from an exciting group of scholars at the cutting edge of their fields to present a multi-disciplinary look at how international law shapes behavior. Contributors present overviews of the progress established fields have made in analyzing questions of interest, as well as speculations on the questions or insights that emerging methods might raise. In some chapters, there is a focus on how a particular method might raise or help answer questions, while others focus on a particular international law topic by drawing from a variety of fields through a multi-method approach to highlight how these fields may come together in a single project. Still others use behavioral insights as a form of critique to highlight the blind spots and related mistakes in more traditional analyses of the law. Throughout this volume, authors present creative, insightful, challenges to traditional international law scholarship.